2020
DOI: 10.3390/brainsci10110766
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypic Spectrum of 47 Czech Patients with Single, Large-Scale Mitochondrial DNA Deletions

Abstract: Background: In this retrospective study, we analysed clinical, biochemical and molecular genetic data of 47 Czech patients with Single, Large-Scale Mitochondrial DNA Deletions (SLSMD). Methods: The diagnosis was based on the long-range PCR (LX-PCR) screening of mtDNA isolated from muscle biopsy in 15 patients, and from the buccal swab, urinary epithelial cells and blood in 32 patients. Results: A total of 57% patients manifested before the age of 16. We did not find any significant difference between paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(70 reference statements)
3
6
2
Order By: Relevance
“…However, the clinical suspicion of KSS in the early stages of the disease may be complicated due to overlapping phenotypes. The occurrence of multisystem presentation in our patient was observed before the age of 10 and this is consistent with reported data (Anteneová et al, 2020; Mancuso et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…However, the clinical suspicion of KSS in the early stages of the disease may be complicated due to overlapping phenotypes. The occurrence of multisystem presentation in our patient was observed before the age of 10 and this is consistent with reported data (Anteneová et al, 2020; Mancuso et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The described data for the population of Polish patients are similar to the findings from other studies [ 18 ] with respect to the clinical syndromes and genetic background and we did not observe any ethnic differences [ 19 , 20 ]. However, this is a wide analysis of Polish patients with progressive external ophthalmoplegia which provides numerous significant findings for both clinicians and geneticists.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the majority of mutations were confirmed in the muscle samples. In some cases, other tissues like urinary sediment cells, oral mucosal epithelium, or hair follicle cells may also be used [ 18 ]. After excluding the most common point mutations and mtDNA rearrangements it is possible to sequence the entire mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic findings, methodology, and results of the mtDNA analysis in the proband have formed part of a recent report that summarizes the clinical data in 20 Czech patients with KSS spectrum. However, an individual case presentation including detailed ocular findings has not been reported [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proband, which is known to carry a single ~6.5 kB mtDNA deletion in blood, buccal smear, and urinary epithelial cells [ 10 ], underwent a general systemic evaluation and detailed ophthalmic examination. This included measurements of the best corrected visual acuity (BCVA) extrapolated to decimal values using Snellen charts, noncontact specular microscopy (Noncon ROBO Pachy SP-9000, Konan Medical Inc., Tokyo, Japan), static perimetry (M700, Medmont International, Nunawading, Australia), and spectral domain optical coherence tomography (SD-OCT; Spectralis, Heidelberg Engineering GmbH, Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%